The Effects of Exercise Induced Muscle Damage on Knee Joint Torque and Balance Performance - Nicole C. Dabbs; Harish Chander (MDPI AG, 2018)
The purpose of this investigation is to determine the effects of exercise induced muscle damage (EIMD) on balance and knee joint torque. Thirteen males and females volunteered to participate in the study. Following a familiarization session, baseline measures were obtained for isometric torque measured during a maximal voluntary isometric contraction (MVIC) for knee flexors and extensors, and ankle dorsi-flexors and plantar-flexors. Additionally, balance performance was tested in double leg (DL), and right single leg (RSL) static and dynamic unstable stability was measured. Participants then performed the muscle damage protocol of front loaded Bulgarian split squats. All measurements were re-assessed for torque and balance immediately and up to 72 h afterwards. A one-way repeated-measures analysis of variance (ANOVA) was used to analyze differences between baseline and all time-points for torque and balance measures. There was a significant time effect for knee extensors MVIC torque, where baseline measures are greater than post EIMD, 24 h and 48 h post EIMD. There was no significant time effect for all balance conditions. These results provide evidence of EIMD following high intensity eccentric exercises with significant reductions in knee extensor torque up to at least 48 h and show that balance was not compromised following EIMD.